The Utilization of Fintech to Increase Financial Inclusion in Indonesia: A Conceptual Paper - Candy Candy; Venessa Venessa; Cedrich Zakhariah; Vincent Vincent (SEIKO : Journal of Management & Business, 2022)
Abstract Financial inclusion has been an economic drawback for many countries, including Indonesia. Developing countries struggle with financial inclusion due to various factors. This paper aims to provide evidence on expanding Indonesia’s financial inclusion through the utilization of Fintech. Studies from previous researchers as secondary data were conceptualized, and to provide complete research, primary data were also gathered to study Indonesian’s response to the theories being hypothesized. This paper elaborates on how Fintech is an alternative in improving accessibility to financial services. It educates and raises awareness to its citizens, eliminates negligence and vulnerability of scams, facilitates credit activities and scores through advanced analytics. It also encourages the efficiency of asset allocation and economic growth and innovation - all of which ultimately leads to the expansion of financial inclusion. Keywords: financial inclusion, Fintech, money circulation, and innovation